Strategi Pengembangan Kecerdasan Spiritual Anak Usia Dini melalui Integrasi Kegiatan Pembelajaran dan Keagamaan - Irma Rismayana; Musyafa Ali (Lembaga Yasin AlSys, 2026)
Spiritual intelligence is an essential dimension of moral and religious development in early childhood that needs to be fostered in balance with intellectual intelligence, although some parents’ perceptions still tend to emphasize children’s intelligence in terms of IQ. This study aims to analyze strategies for developing the spiritual intelligence of young children through the integration of learning and religious activities at TK Prima Sakinah Islamic School in Bekasi City. A qualitative approach with field research was employed, with data collected through nonparticipant observation, semi-structured interviews, and documentation, and analyzed using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. The findings show that children’s spiritual intelligence is developed through the integration of religious habituation, worship practices, Islamic-value-based social interaction, narrative activities, simple religious projects, dzikir pagi (morning remembrance), habituation of adab, and the creation of an Islamic learning environment. These integrative strategies have been shown to foster children’s awareness of God, Islamic adab, moral value internalization, and consistent religious behavior in daily life. The study concludes that systematically designed integration of learning and religious activities is effective in developing the spiritual intelligence of young children. The implications underscore the importance of holistic learning designs that continuously integrate pedagogical and spiritual dimensions as theoretical and practical references for Islamic early childhood education institutions.